PEMETAAN DAN STRATEGI PEMANFAATAN TEKNOLOGI PADA INDUSTRI OLAHAN RUMPUT LAUT INDONESIA YANG BERKELANJUTAN - Hasibuan, Sawarni (Operations Excellence: Journal of Applied Industrial Engineering, 2016)
Abstract. The fisheries industrialization program tries to place the downstreaming of seaweed as one of the strategies to increase the added value of the seaweed commodity. However, the competitiveness of the national seaweed industry is also relatively low compared to foreign industry. One of the problems of the competitiveness of the processed seaweed industry is because the extent of the use of technology in the processed seaweed industry has not been identified. The purpose of this research is to map the use of technology in the processed seaweed industry in downstreaming a competitive and sustainable Indonesian seaweed industry. The mapping of the existing condition of technology utilization refers to five indicators, namely production aspect, cost aspect, HR aspect, energy aspect, and environmental aspect. The development strategy of the seaweed downstream industry is developed by using the SWOT method. The recommended technology standard analysis is based on the benchmark method. Results of the analysis shows that the dominant type of technology used is the „semi-mechanical technolgy‟ which mostly comes from Europe/America followed by Japan, local, and China. In order to increase the competitiveness and sustainability of the Indonesian processed seaweed industry, improvements in the fields of artificial drying, high value added (downstream) technology and technology for food safety is required. Several action plans required among others are: the solar system dryer in the upstream industry, the implementation of quality and food safety management system in the production chain, identification and investment of high value products in the seaweed downstream industry. Keywords: seaweed, technology assessment, SWOT, upstream and downstream industry